Probing Selectivity and Creating Structural Diversity Through Hybrid Polyketide Synthases. (5th June 2020) - Koch, Aaron A.; Schmidt, Jennifer J.; Lowell, Andrew N.; Hansen, Douglas A.; Coburn, Katherine M.; Chemler, Joseph A.; Sherman, David H.
Abstract: Engineering polyketide synthases (PKS) to produce new metabolites requires an understanding of catalytic points of failure during substrate processing. Growing evidence indicates the thioesterase (TE) domain as a significant bottleneck within engineered PKS systems. We created a series of hybrid PKS modules bearing exchanged TE domains from heterologous pathways and challenged them with both native and non‐native polyketide substrates. Reactions pairing wildtype PKS modules with non‐native substrates primarily resulted in poor conversions to anticipated macrolactones. Likewise, product formation with native substrates and hybrid PKS modules bearing non‐cognate TE domains was severely reduced. In contrast, non‐native substrates were converted by most hybrid modules containing a substrate compatible TE, directly implicating this domain as the major catalytic gatekeeper and highlighting its value as a target for protein engineering to improve analog production in PKS pathways. Abstract : Improved catalysis with engineered polyketide synthases : Pairing wild‐type polyketide synthases with non‐native substrates largely failed to produce the anticipated products. A series of hybrid modules bearing heterologous thioesterase domains were generated and employed to alleviate the observed catalytic bottleneck, resulting in the efficient processing of non‐native substrates and an unexpected path to product diversity.